MAHMUD YUNUS DAN PEMIKIRANNYA DALAM PENDIDIKAN - Zulmardi Zulmardi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
As an innovator in educational thought in Indonesia, Mahmud Yunus has pioneered several innovated works. Among his innovated thoughts in education, especially in terms of educational institution are: grading the education levels in accordance with the age of pupils, establishing PGA (senior high schools for Islamic teaching teacher training), and ADIA (Academy of Islamic Studies) in Jakarta. In terms of teaching methods, Mahmud Yunus pioneered the application of Directs Methods (thariqal al- mubasyarah), in teaching Arabic. On of his important ideas deal with the nation that